ANALISIS FAKTOR RISIKO OBESITAS PADA BALITA DI POLI ANAK RSU AULIA JAKARTA SELATAN TAHUN 2025 - Dita Aprillia; Siti Syamsiah; Rosmawaty Lubis (LPPM Universitas Abdurrab, 2026)
Obesity among toddlers is an increasing global health problem, including in Indonesia. The prevalence of overweight in early childhood has risen from 5.6% in 2018 to 6.1% in 2022. This increase has important implications for young children, particularly by raising the risk of cognitive, language, and behavioral developmental disorders, which may affect school readiness and long-term growth and development. South Jakarta has been identified as the area with the highest prevalence of overweight toddlers (7%), exceeding East Jakarta, North Jakarta, and Central Jakarta, highlighting the need to investigate underlying vulnerability factors. This study aimed to analyze the determinants of overweight among toddlers at the Pediatric Clinic of Aulia General Hospital, South Jakarta, in 2025. A mixed-methods approach with a sequential explanatory design was applied. The quantitative phase employed a cross-sectional design involving 137 mother–toddler pairs aged ≥1–≤5 years, selected using purposive sampling. Data were analyzed using chi-square tests and multiple logistic regression. The qualitative phase consisted of in-depth interviews with eight key informants selected through snowball sampling and analyzed thematically using source triangulation. The findings showed that carbohydrate and fat intake, eating frequency, portion size, maternal knowledge, family history of obesity, socioeconomic status, and physical activity were significantly associated with the risk of obesity among toddlers (p < 0.05). Multivariate analysis identified family history of obesity as the dominant factor (Beta = 0.373). In conclusion, toddler obesity is mainly influenced by dietary patterns and physical activity, emphasizing the importance of balanced nutrition education and early promotion of physical activity as preventive strategies